The Potential Of Instant Red Bean Porridge Phaseolus vulgaris L For MP-ASI Companion To Baby Growth - Cahyaning Rini Utami; Maftuhatuz Zakiyah Darojah; Deny Utomo (Publikasi Indonesia, 2024)
Phaseolus vulgaris L. are one of the plant-based food sources rich in nutrients and protein. Red beans contain protein (23.1%), carbohydrates (59.5%), calcium, phosphorus, iron, vitamin A, vitamin B1, and bioactive components such as flavonoids and phytosterols. Instant porridge is a complementary food for breastfeeding infants (known as MP-ASI) that is essential to meet the nutritional needs of babies during their growth phase. Red beans have the potential to be used as a raw material for making instant porridge as a complementary food for breastfeeding. Consuming red beans raw is not advisable, as they still contain several anti-nutritional compounds such as phytic acid, hemagglutinin, antitrypsin, and goitrogens that can hinder the digestion nutritional components. Therefore, a cooking process necessary to eliminate these anti-nutritional compounds, which can include soaking, boiling, and mold fermentation. The research design employed in this study is a literature review with a qualitative descriptive approach, utilizing content analysis methodology that references the analyzed journal manuscripts. Secondary data used in this literature review were obtained from previous research studies. The data sources utilized, namely articles and journals, were obtained from Google Scholar. The results of this literature review reveal the nutritional content present in instant red bean porridge and the potential of instant red bean porridge as a complementary food for breastfeeding. The nutritional content found in instant red bean porridge includes carbohydrates (49.95%), protein (18.79%), fiber (16.54%), and fat (1.20%). Furthermore, instant red bean porridge also contains various antioxidants such as flavonoids, tannins, saponins, triterpenoids, and coumarins.